Uncovering the complexity of source mechanism in an anisotropic coal mine using sequential inversion - Chun-Hui Song; Cai-Ping Lu; Xiu-Feng Zhang; Chao Wang; Jie-Fang Song; Yang Liu; Shi-Dong Li; Dapeng Zhao (Scientific Reports)
Abstract Accurate characterisation of seismic source mechanisms in mining environments is crucial for effective hazard mitigation, but it is complicated by the presence of anisotropic geological conditions. Neglecting anisotropic effects during moment tensor (MT) inversion introduces significant distortions in the retrieved source characteristics. In this study, we investigated the impact of ignoring anisotropy during MT inversion on the reliability of hazard assessment. We investigated a high-energy (2.18 $$×$$ 106 J) induced by mining activities in the Nantun coal mine in China. The subsurface was modelled as a vertically transversely isotropic medium, incorporating four different levels of anisotropy derived from site-specific geological and tomographic data. The results demonstrate that neglecting anisotropy led to significant distortions in the retrieved source parameters, including polarity flips and the introduction of spurious non-double-couple components. These artefacts compromised the accuracy of hazard analysis and undermined the effectiveness of risk management strategies. In contrast, the sequential inversion method yields a MT solution with a 0.14 misfit, accurately retrieving the focal mechanism, which is interpreted as a normal right-lateral oblique shear failure along the F3 fault. This study highlights the importance of properly incorporating anisotropy effects when analysing induced seismicity in heterogeneous mining environments. The use of a homogeneous Green’s function for MT inversion may be inadequate for reliable hazard assessment, underscoring the need for advanced techniques that can effectively model the influence of subsurface anisotropy on seismic wave propagation and source retrieval.